Potential Application of Egg White Peptides for Antioxidant Properties: Perspectives from Batch Stability and Network Pharmacology - Siwen Lyu; Ting Li; Qi Yang; Jingbo Liu; Ting Zhang; Ting Yu (Foods)
This study investigated the batch stability of egg white peptides (EWPs) during the enzymatic hydrolysis process, and confirmed the potential application of four crucial four peptides inoxidative damage repair. The results revealed that different batches of EWPs had good stability relating to antioxidant activity. With a similar sequence to confirmed antioxidant peptides, four EWPs (QMDDFE, WDDDPTD, DEPDPL, and FKDEDTQ) were identified withhigh repetition rates, and their potential to repair oxidative damage was investigated. Network pharmacology results showed that these four peptides could regulate the targets related to oxidative damage. Enrichment results demonstrated that these four peptides could influence the targets and pathways related to glutathione transferase activity (enrichment score: 148.0) and glutathione metabolism (p value: 9.22 × 10−10). This study could provide evidence for the batch stability of hydrolyzed prepared EWPs, and offer theoretical support for the development of antioxidant damage ingredients derived from foods.